Urgensi Pengaturan Penerbitan Covernote Oleh Notaris sebagai Upaya Pencegahan Penyalahgunaan dalam Pemberian Fasilitas Kredit - Monica Ade Wulantari; Subekti Subekti; Itok Dwi Kurniawan (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to examine the legal position of  covernotes in the provision of bank credit facilities and the urgency of regulating their issuance by Notaries as a measure to prevent abuse. This research is important because the practice of issuing  covernotes is often used as a basis for credit disbursement, even though, legally,  covernotes are not authentic deeds and do not possess the evidentiary power of authentic notarial acts. This condition creates potential risks of misuse by both banks and Notaries, as well as legal uncertainty for all parties involved. The study employs a normative legal research method with a statute approach and case approach. The legal materials utilized include primary, secondary, and tertiary sources, collected through library research. Analysis is conducted qualitatively through interpretation of the processed legal materials. The results indicate that  covernotes function solely as temporary and informative administrative statements, clarifying that the process of credit collateral registration is still underway.  covernotes cannot be regarded as valid collateral evidence; therefore, in the event of default, the bank cannot execute the collateral before the authentic deed is issued. These findings underscore the critical need for clear regulation of  covernotes by Notaries to ensure legal certainty, prevent abuse of authority, and protect the interests of debtors, creditors, and Notaries themselves. With clear regulation,  covernotes can continue to serve as an effective administrative instrument without creating legal risks or conflicts of interest in the credit provision process.